2022
DOI: 10.1002/gj.4427
|View full text |Cite
|
Sign up to set email alerts
|

Palaeozoic tectonic evolution and magmatism in the Kalatag area, East Tianshan, NW China: Evidence from the geochronology and geochemistry of intrusive rocks

Abstract: The Kalatag area contains many intrusive rocks of Late Ordovician to Permian age and hosts polymetallic deposits that are associated with magmatism. It is a key area for revealing the nature and genesis of the Palaeozoic rocks in East Tianshan. The intrusive rocks of different periods preserve useful information regarding the tectonomagmatic history of the Kalatag area. Zircon U–Pb geochronological, Hf isotopic, Sr–Nd isotopic, and whole‐rock geochemical analyses are reported for the intrusions from the Meilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
(186 reference statements)
0
2
0
Order By: Relevance
“…The intermediate felsic dikes are well developed in the Fengtai orefield. The major intrusions are the Xiba and the Huahongshuping granitic plutons, which are distributed in the central part of the Fengtai orefield and are basically consistent with the direction of the main structural line (NW direction) within the area [6,9] (Zhang, 2010;Hu, 2015). The largest Xiba pluton is mainly composed of granodiorite, quartz diorite, and monzogranite, with hornstone and andalusite developed in the outer contact zone.…”
Section: Regional Geological Settingmentioning
confidence: 62%
See 1 more Smart Citation
“…The intermediate felsic dikes are well developed in the Fengtai orefield. The major intrusions are the Xiba and the Huahongshuping granitic plutons, which are distributed in the central part of the Fengtai orefield and are basically consistent with the direction of the main structural line (NW direction) within the area [6,9] (Zhang, 2010;Hu, 2015). The largest Xiba pluton is mainly composed of granodiorite, quartz diorite, and monzogranite, with hornstone and andalusite developed in the outer contact zone.…”
Section: Regional Geological Settingmentioning
confidence: 62%
“…The largest Xiba pluton is mainly composed of granodiorite, quartz diorite, and monzogranite, with hornstone and andalusite developed in the outer contact zone. A combination of previous zircon U-Pb ages indicate that the granitic complex intruded between 219 and 215 Ma [9][10][11]. The previous geochronoloical and geochemical data suggested that the Xiba pluton was formed in the Late Indosinian period, and was emplaced under the post-collision setting after the collision between the North China Craton and the Yangtze Craton along the Mianlue suture zone [1,12,13] The Shuangwang large gold deposit is developed approximately 5 km north of the Xiba pluton, and the Yinmusi medium-sized lead-zinc deposit is developed approximately 15 km in the NW direction.…”
Section: Regional Geological Settingmentioning
confidence: 71%